Energy Security Assessment of Nepal for the Period 2005-2030 - Darlamee, Shova; Bajracharya, Tri Ratna (Journal of Advanced College of Engineering and Management, 2021)
Energy is an important driver of all economic activities and it is necessary for the production of goods and the provision of services. Thus, a secure supply of energy to meet national demand on both the short term and long term is important for any country. As a net importer of petroleum products from only one supplier country of petroleum products (i.e. India), supply and demand gap of energy, frequent price fluctuations of petroleum products and poor diversification of primary energy supply, policies regarding energy security should be developed for Nepal.  This study aims to assess the energy security index of Nepal so as to provide a picture of the historical performance of the country in terms of energy security for the past years 2005-2015 and in the future 2016-2030 under different scenarios. A set of 24 energy security indicators were selected based on literature review and relevant to national energy policies and grouped under 5 dimensions which are availability, affordability, accessibility, efficiency and acceptability. It can be seen that energy security for Nepal has been following a declining trade since 2005/06 to 2015/16, the causes of which could be attributed to the increase in energy consumption, increase in imports of petroleum products, increase in electricity deficit from the year 2008/09, increase in price of petroleum products. However, the value of energy security index is on the higher side (near to 10) which is mainly due to the fact that energy supply of Nepal is mostly dependent on traditional sources which is domestically supplied. There is a need to incorporate energy security in the national energy policy of Nepal with more emphasis on diversification of primary energy sources (other than traditional resources), reduction on import dependency especially on fossil fuel resources, strategic fuel reserves, diversification of energy resources uses in different energy consumption sectors like transport, industries, increase in energy supply from renewable energy sources, etc.